Forced out: a Nikkei woman's search for a home in America - Kawamota, Judy Y., author; University Press of Colorado, publisher (Colorado State University. Libraries, 2020)
Voluntary evacuation,' a little-known Japanese American experience during World War II with roughly 120,000 people forced from their homes by Executive Order 9066. Around 5,000 escaped. Recounting her family's flight from home and the influence of those experiences. Like many families who lost everything and started over in hostile environments.--Provided by publisher.
Battlefield to Beet Field: The Germans Meet Dad in World War II -- A Better Mousetrap -- Mind the Gap: Locating Missing Memories -- Big Apple to Big Sky: Meditations on Space -- The One and Only -- Crossing Over -- Saints and Sinners -- Cape Town to Japantown -- Chicken, Waffles, and . . . Tsukemono -- Pictures on the Wall -- Epilogue: Bananas and Beyond.
Keywords: Japanese Americans -- Biography; Japanese American women -- Biography; Japanese Americans -- Evacuation and relocation, 1942-1945; World War, 1939-1945 -- Personal narratives, Japanese American; Japanese Americans -- Social conditions -- 20th century; Psychotherapists -- United States -- Biography; Social workers -- United States -- Biography; Kawamoto, Judy